Homesickness as Seen in Harry Potter’s Character in J. K. Rowling’s Harry Potter and the Prisoner of Azkaban - Januar Ramadhan; Rahmawan Jatmiko (Universitas Gadjah Mada, 2019)
This research attempts to examine the effects of homesickness on Harry potter in J. K. Rowling’s Harry Potter and the Prisoner of Azkaban. Homesickness as a mental illness is prevalent in people; therefore, the investigation used Harry Potter as its subject. The research adopts the theory of homesickness proposed by Fisher (1989). The research shows the harshness of being homesick in a society that we have little control of and in situations where we have no choice on how to proceed. It highlights the need of attachments in a social sense for individuals who are suffering from homesickness because it is one of the definite cure for a serious and dangerous mental illness. It can affect anyone regardless of age, living conditions, and state of mind.